2020
DOI: 10.1007/s10344-020-01425-7
|View full text |Cite
|
Sign up to set email alerts
|

Bear trade in the Czech Republic: an analysis of legal and illegal international trade from 2005 to 2020

Abstract: There is a large demand for bear parts in the Czech Republic, and this drives legal and illegal trade in various bear species sourced from outside the country. From 2010 to 2018, the Czech Republic reported legal imports of 495 bear parts, mostly as trophies from Canada and Russia. Illegal trade in bear parts and derivatives for medicine as well as trophies persists as evidenced by the number of seizures made by the Czech Environmental Inspectorate during this same period. From January 2005 to February 2020, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This is consistent with the findings of Foley et al (2011) and Burgess et al (2014) in their assessment of the bear trade in Asia. While China and South Korea were implicated as primary destinations of illicit gall bladders and paws in this study, Russian sourced bear parts and medicinal derivatives have also been seized in/ smuggled to Australia and New Zealand (Cassey et al 2021), Czech Republic (Shepherd et al 2020), Japan (Kumi and Sakamoto, 2002), Malaysia (Lee et al 2015), Vietnam (Willcox et al 2016) and Poland (Gomez et al in prep), indicating the potential global nature of the illegal trade of bear parts from Russia (Figure 3). Of further interest, China is not only a key destination of bear parts in trade but also a key source of bear parts found in trade in Southeast Asia (Foley et al 2011, WAP 2018).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This is consistent with the findings of Foley et al (2011) and Burgess et al (2014) in their assessment of the bear trade in Asia. While China and South Korea were implicated as primary destinations of illicit gall bladders and paws in this study, Russian sourced bear parts and medicinal derivatives have also been seized in/ smuggled to Australia and New Zealand (Cassey et al 2021), Czech Republic (Shepherd et al 2020), Japan (Kumi and Sakamoto, 2002), Malaysia (Lee et al 2015), Vietnam (Willcox et al 2016) and Poland (Gomez et al in prep), indicating the potential global nature of the illegal trade of bear parts from Russia (Figure 3). Of further interest, China is not only a key destination of bear parts in trade but also a key source of bear parts found in trade in Southeast Asia (Foley et al 2011, WAP 2018).…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, brown bear trophies are illegally exported from Russia as well. A recent study on the illegal bear trade in the Czech Republic found that Russia was one of the largest exporters of bear trophies to the Czech Republic both legally and illegally (Shepherd et al 2020). Similar findings were noted in Poland (Gomez et al, in prep).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Canada has been identified as one of the largest (re)exporters of Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES)-listed species that are carriers of at least one zoonotic disease (UNEP-WCMC and JNCC 2021). Canada also plays a role as an intermediary, for example in relation to trade in marine aquarium animals and live hoofstock to the US (Rhyne et al 2017;Smith et al 2017), the legal and illegal trade of bear parts to countries such as the Czech Republic (Shepherd et al 2020), Australia, and New Zealand , and the trade in ball pythons (Python regius) as exotic pets from West Africa (D'Cruze et al 2020c). The overall average annual financial value of the legal live wild animal trade in Canada from 2016 to 2020 was estimated at $85.7 million CAD for exportations and $100.6 million CAD for importations (Government of Canada 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The illegal products from other tiger-ranging countries make their way to China via an international trading network. Trafficked tiger products are primarily used as decorative materials or as an ingredient in Chinese traditional medicines (Shepherd et al, 2020 ; van Uhm, 2020 ; Wong, 2019 , 2020 ) and the production of wine (Coals et al, 2020 ; Wong, 2016 ). Skin, claws, and teeth are part of fashion items, home decor, jewellery, holy materials, and the symbol of bravery.…”
Section: Introductionmentioning
confidence: 99%